Ex-ante Carbon-balance Value Chain tool (EX-ACT VC) to assess the rice value chain’s environmental and socio-economic impact - CGIAR Research Program on Rice (2021)
The Ex-ante Carbon-balance Value Chain tool (EX-ACT VC) developped by FAo in 2016 has being adapted to assess the rice value chain’s environmental and socio-economic impact. The tool is ready to be used by the NARS partners to develop rice value chain development model in their countries.